Life on the European periphery. Iceland’s hesitancy to take full part in the European project - Ingþór Árnason 1995- (2022)
Iceland has been reluctant to fully integrate with the European project throughout the previous decades. Numerous reasons are believed to be behind the partial integration of the island state, such as its fishing industry, the EEA agreement among other factors like agriculture, sovereignty and relations to the United States. Primarily using the method of process tracing and the theoretical lenses of liberalism and differentiation, this thesis adds to the discussion on the current situation of Iceland’s European integration. The Icelandic fishing industry, agricultural industry, the beneficial EEA agreement and its political relationship with the United States all have an impact on why Iceland chooses to only partially integrate with the European project. It can be presumed that all these factors need to change for Iceland to move closer to full integration.